Impact of Acute HIV Infection and Early Antiretroviral Therapy on the Human Gut Microbiome. (21st August 2019) - Sortino, Ornella; Phanuphak, Nittaya; Schuetz, Alexandra; Ortiz, Alexandra M; Chomchey, Nitiya; Belkaid, Yasmine; Davis, Jacquice; Mystakelis, Harry A; Quiñones, Mariam; Deleage, Claire; Ingram, Brian; Rerknimitr, Rungsun; et al.
Abstract: Background: Intestinal microbial dysbiosis is evident in chronic HIV-infected individuals and may underlie inflammation that persists even during antiretroviral therapy (ART). It remains unclear, however, how early after HIV infection gut dysbiosis emerges and how it is affected by early ART. Methods: Fecal microbiota were studied by 16s rDNA sequencing in 52 Thai men who have sex with men (MSM), at diagnosis of acute HIV infection (AHI), Fiebig Stages 1–5 (F1-5), and after 6 months of ART initiation, and in 7 Thai MSM HIV-uninfected controls. Dysbiotic bacterial taxa were associated with relevant inflammatory markers. Results: Fecal microbiota profiling of AHI pre-ART vs HIV-uninfected controls showed a mild dysbiosis. Transition from F1-3 of acute infection was characterized by enrichment in pro-inflammatory bacteria. Lower proportions of Bacteroidetes and higher frequencies of Proteobacteria and Fusobacteria members were observed post-ART compared with pre-ART. Fusobacteria members were positively correlated with levels of soluble CD14 in AHI post-ART. Conclusions: Evidence of gut dysbiosis was observed during early acute HIV infection and was partially restored upon early ART initiation. The association of dysbiotic bacterial taxa with inflammatory markers suggests that a potential relationship between altered gut microbiota and systemic inflammation may also be established during AHI. Abstract : Gut dysbiosis was detected during early acute HIV infection in Thai MSM and was partially restored after 6 months of antiretroviral therapy. Bacterial changes were subtle but significant correlations were observed between pathogenic taxa and systemic inflammatory biomarkers.